2021
DOI: 10.1128/mra.01224-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of a Polymyxin-Resistant Klebsiella pneumoniae Clinical Strain Carrying mcr-8.1 and bla NDM-5

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a major threat to global health. Here, we report the draft genome sequence of a Klebsiella pneumoniae clinical strain carrying mcr-8.1 and blaNDM-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…The mcr-8 homolog is predominant in our collection, with mcr-1 being the second most common. Unlike the situation in Australia ( 3 ), cocarriage of the carbapenemase gene and mcr was rare in this study, occurring in only one isolate; however, the infected patient was dead in this study ( 15 ).…”
Section: Discussioncontrasting
confidence: 73%
“…The mcr-8 homolog is predominant in our collection, with mcr-1 being the second most common. Unlike the situation in Australia ( 3 ), cocarriage of the carbapenemase gene and mcr was rare in this study, occurring in only one isolate; however, the infected patient was dead in this study ( 15 ).…”
Section: Discussioncontrasting
confidence: 73%
“…Since the mcr-8.1 gene from pig-derived K. pneumoniae strain KP91 was first reported in 2018, multiple mcr-8 variants have been identified, ranging from mcr-8.2 to mcr-8.5 ( Sun et al., 2020 ). Currently, K. pneumoniae producing both MCR-8 and NDM has emerged, such as mcr-8.1 and bla NDM-1 (animal origin), mcr-8.2 and bla NDM-1 (human origin), mcr-8.1 and bla NDM-5 (human origin), and mcr-8.5 and bla NDM-5 (animal origin) ( Wang et al., 2018 ; Ma et al., 2020a ; Sun et al., 2020 ; Pei et al., 2021 ). In our study, we also identified the K. pneumoniae isolate co-harboring mcr-8.2 and bla NDM-5 in the lung transplantation ward, and should be alerted to its in-hospital spread.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, K. pneumoniae producing both MCR-8 and NDM has emerged, such as mcr-8.1 and bla NDM-1 (animal origin), mcr-8.2 and bla NDM-1 (human origin), mcr-8.1 and bla NDM-5 (human origin), and mcr-8.5 and bla NDM-5 (animal origin) (30)(31)(32)(33). In our study, we also identified the K. pneumoniae isolate co-harboring mcr-8.2 and bla NDM-5 in lung transplantation ward, and should be alerted to its in-hospital spread.…”
Section: Discussionmentioning
confidence: 99%